Executive Functioning, Reward/Punishment Sensitivity, and Conduct Problems in Boys With Callous-Unemotional Traits - Platje, Evelien (International journal of offender therapy and comparative criminology, 2018)
Callous-unemotional (CU) traits are thought to characterize children exhibiting persistent and severe conduct problems (CPs). Reward and punishment sensitivity have often been investigated, yet executive function problems have mostly been studied in adults. Moreover, the level of co-occurring CPs is important to take into account. Therefore, the current study investigated differences in reward responsivity, punishment sensitivity, and executive functioning (EF) between four subgroups of general community boys (N = 346, Mage = 14.01 years, SD = 1.19): high CU/high CP, low CU/high CP, high CU/low CP, and low CU/low CP. Boys with high CU/high CP showed significantly more EF problems, but similar reward and punishment sensitivity as low CU/high CP boys. Boys with high CU/low CP did not differ from low CU/low CP boys. Severity of executive function problems appears to distinguish boys who show a combination of CU-traits and CPs from boys with CPs alone.